2018
DOI: 10.1039/c8sc01814f
|View full text |Cite
|
Sign up to set email alerts
|

Combined scanning electrochemical and fluorescence microscopies using a tetrazine as a single redox and luminescent (electrofluorochromic) probe

Abstract: Combined fluorescence and electrochemical microscopies using a single redox and fluorescent probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Luminescent switches and displays were created with electrofluorochromic compounds . Redox‐active fluorescent molecules have served as probes for elucidating the catalytic processes in biomimetic reactions and charge carrier traps in organic electronic devices . Recently, electrofluorochromism at the single‐molecule level was achieved based on inelastic tunneling of electrons between a scanning transmission electron microscope (STEM) tip and a gold electrode .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luminescent switches and displays were created with electrofluorochromic compounds . Redox‐active fluorescent molecules have served as probes for elucidating the catalytic processes in biomimetic reactions and charge carrier traps in organic electronic devices . Recently, electrofluorochromism at the single‐molecule level was achieved based on inelastic tunneling of electrons between a scanning transmission electron microscope (STEM) tip and a gold electrode .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Redox-active fluorescent molecules have served as probes for elucidating the catalytic processes in biomimetic reactions and charge carrier traps in organic electronic devices. [21][22][23][24][25] Recently, electrofluorochromism at the single-molecule level was achieved based on inelastic tunneling of electrons between a scanning transmission electron microscope (STEM) tip and a gold electrode. [26] Nondestructive fluorescence memory may also be created using electrofluorochromism because electrochemical inputs are orthogonal to fluorescence processes, thereby enabling reversible write-read-erase memory cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical fluorophores, such as resazurin and tetrazines, used as respiration indicators to study bacteria and biofilm behaviour [130], have been tested as redox mediators. Guerret-Legras et al [131,132] showed that the fluorescence intensity of these molecules is a function of the potential of the SECM probe, independent of the substrate potential with the tip-substrate distance controlling the fluorescence amplitude. Hence, electrochemically induced processes in biological and microbial samples could be investigated with high spatial resolution.…”
Section: Future Potential Of Hybrid Secm Techniquesmentioning
confidence: 99%
“…The atomic force microscope has been successfully integrated with different optical microscopy techniques [9][10][11] , allowing to overcome some of its individual limitations when it comes to, for instance, sample penetration and biological specificity. In this regard, AFM has been combined with Confocal Laser Scanning Microscopy (CLSM) [12][13][14] , Aperture Correlation Microscopy 8 , Total Internal Reflection Fluorescence Microscopy (TIRFM) [15][16][17][18][19][20][21] , and Fluorescence Lifetime Imaging (FLIM) 22,23 .…”
mentioning
confidence: 99%